Enlightening gallium nitride-based UV photodetectors. Issue 36 (28th August 2020) - Aggarwal, Neha; Gupta, Govind
Abstract : This article highlights the emerging demand for gallium nitride (GaN) semiconductor technology that offers superior optoelectronic properties making it suitable for futuristic ultraviolet (UV) photodetection applications. Abstract : This article highlights the emerging demand for gallium nitride (GaN) semiconductor technology that offers superior optoelectronic properties making it suitable for highly efficient ultraviolet (UV) photodetection devices. An overview of the required physical mechanisms and a background review of the latest approaches for highly responsive GaN-based UV photodetectors are compiled and the future perspective for optoelectronic devices is discussed. It was proposed that the GaN subfield is directed towards integration with two-dimensional materials for futuristic applications. Finally, this article provides open questions for future researchers and suggests a direction for possible solutions to the problems faced during the development of highly efficient optoelectronic devices.